Proses Penentuan Penerima Zakat, Infaq, dan Shadaqah pada Lembaga Amil Zakat di Surabaya - Yayan Firmansah (University of Darussalam Gontor, 2015)
Zakat, infaq, and shadaqah (ZIS) are the important instruments in Islamic Economic. Especially zakat, it can be seen from the states of zakat with sholat in 29 verses of Al Quran. Because ZIS is estimable in empowering the society economy, it has to be well managed by zakat administrator institution. Therefore, for achieving that goal, zakat administrator institution has to be able in determining people who have rights to receive zakat to avoid zakat distribution overlapping. This research has a goal in identifying the determination of zakat receivers (mustahiq) in zakat administrator institution in Surabaya. There are four research objects: Dompet Dhuafa Republika, Pos Keadilan Peduli Umat, Yayasan Dana Sosial Al Falah, and Baitul Maal Hidayatullah. It will use descriptive qualitative as the research approach. The results of this research conclude that each zakat administrator institution has different criteria of zakat receivers, especially in poor and needy people criteria. The differences can be seen from the standard of poverty used by zakat administrator institution.